Meningkatkan Pemahaman Mengenai Baptisan Kepada Pemuda di GBI Silangkitang - Adi Suhenra Sigiro; Sisga Desriman Zebua; Mega Intan Tambunan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
One of the important sacraments in Christianity is the sacrament of baptism. Different denominations or sects also have different understandings of baptism. GBI itself believes that baptism consists of two, namely water baptism and Holy Spirit baptism. In connection with the low understanding of youth at GBI Silangkitang regarding baptism, it is necessary to hold a seminar on the theme of baptism. Before this seminar was held, the writer conducted a literature review, so that the results of the research presented in the seminar had an adequate academic basis. The research results that have been presented in the seminar are that baptism is divided into two, namely water baptism and Holy Spirit baptism. Water baptism is a sign of obedience to God's word, water baptism must follow Christ's example, and water baptism is a sign of being united with the death and resurrection of Christ. Furthermore, the baptism of the Holy Spirit is the baptism carried out by the Lord Jesus into the Holy Spirit. The baptism of the Holy Spirit is God's gift to give power to believers to carry out ministry according to the gifts of the Spirit received by believers and these gifts of the Spirit must be balanced with the fruit of the Spirit. Keywords: ,